ASSESSMENT FOR DATA CORRELATION OF THE DOWNHOLE SEISMIC MEASUREMENT RESULTS ON UNDERGROUND COAL GASIFICATION LOCATION USING MULTIVARIATE ANALYSIS - Zulfahmi Zulfahmi; Zulkifli Pulungan (Indonesian Mining Journal, 2015)
One of the risk potentials that must be alerted for underground coal gasification(UCG) technology is surface subsidence, although such a technology is potential to be developed in Indonesia. Therefore, the characteristics of rock strata above the coal seam needs to be deliberately considered. Downhole seismic data is one of the data that is needed to determine the geotechnical characteristics of the rock layers near the surface. Previously, it is considered that physical, mechanical and dynamic properties of the rocks at same geological formation have equal characteristics although they come from different locations. However, based on correlation test to downhole seismic data using multivariate analysis showed that no significant correlation between the measured data from Macangsakti-1 and Macangsakti-2 with those of Mahayung from different location, although they are in the same geological formation. This fact is shown by the analysis result which shows a significance value of <0.05. Macangsakti-1 and Macangsakti 2, which are located closely, showed a significant value of >0.05. It means that there are no significant data differences between the two locations. It is very likely since there are a lot of factors that affect such conditions, especially the influence of tectonics at each location. In addition, factors of the surface condition such as infiltrations of ground water from the surface towards the unsaturated zone also affect the difference of wave propagation velocity at each location. Thus, it should be noted that the condition of rock layers are site specific to determine the characteristics of the sites it should be measured at the sites and can not be generalized with other locations, although they are in the same geological formation.